Long-term effects of developmental exposure to di-n-butyl-phthalate (DBP) on rat prostate: Proliferative and inflammatory disorders and a possible role of androgens - Scarano, Wellerson Rodrigo [UNESP]; de Toledo, Fabiola Choqueta; Guerra, Marina Trevizan [UNESP]; Pegorin de Campos, Silvana Gisele [UNESP]; Justulin Junior, Luis Antonio; Felisbino, Sergio Luis [UNESP]; Anselmo-Franci, Janete A.; Taboga, Sebastiao Roberto [UNESP]; Kempinas, Wilma de Grava [UNESP] (Elsevier B.V., 2009)
In the present study we evaluated the toxic effects on the male adult rat prostate of DBP exposure during fetal and lactational periods, because although many studies have addressed the influence of phthalates on the male reproductive system, only a few have discussed their possible effects on prostate development. Pregnant females were distributed into two experimental groups: Control (C) and Treated (T). The females of the T group received DBP (100 mg/kg, by gavage) from gestation day 12 to postnatal day 21, while C rats received the vehicle (corn oil). In adulthood (90 days old), the animals were euthanized. The serum and testicular testosterone levels were measured. Ventral prostate was removed and weighed. Distal segment fragments of the ventral prostate were fixed and processed for histochemistry and immunohistochemistry to detect androgen receptor (AR) and Ki67 antigens. Protein extraction from ventral prostate fragments was performed for AR immunoblotting and Gelatin zymography for MMP-2 and MMP-9 (MMP, metalloproteinase). Stereological and histopathological analyses were also performed. Serum and testicular testosterone levels and prostate weight were comparable between groups. In the T group the relative proportions (%) of epithelial (C=32.86; T=42.04*) and stromal (C=21.61; T=27.88*) compartments were increased, while the luminal compartment was decreased (C=45.54; T=30.08*), *p < 0.05. In T, disseminated inflammatory infiltrate in the stroma, associated or not with epithelial dysplasia and PIN (Prostatic Intraepithelial Neoplasia), was observed. Increases in AR expression, proliferation index and metalloproteinase 9 (MMP-9) activity were noted in T animals. In some T animals, collagen fibrils accumulated adjacent to the epithelium. As far as we are aware, this is the first report in the literature showing that phthalates could play a role in proliferative and inflammatory disorders of the rat prostate. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: DBP; Prostate; Inflammation; AR expression; Epithelial proliferation